Artificial Magnetic Conductor as Planar Antenna for 5G Evolution - Komsan Kanjanasit; Pracha Osklang; Terapass Jariyanorawiss; Akkarat Boonpoonga; Chuwong Phongcharoenpanich (My University, 2022)
A 5G wireless system requests a high-performance compact antenna device. This research work aims to report the characterization and verification of the artificial magnetic conductor (AMC) metamaterial for a high-gain planar antenna. The configuration is formed by a double-side structure on an intrinsic dielectric slab. The 2-D periodic pattern as an impedance surface is mounted on the top surface, whereas at the bottom surface the ground plane with an inductive narrow aperture source is embedded. The characteristic of the resonant transmission is illustrated based on the electromagnetic virtual object of the AMC resonant structure to reveal the unique property of a magnetic material response. The characteristics of the AMC metamaterial and the planar antenna synthesis are investigated and verified by experiment using a low-cost FR4 dielectric material. The directional antenna gain is obviously enhanced by guiding a primary field radiation. The loss effect in a dielectric slab is essentially studied having an influence on antenna radiation. The verification shows a peak of the antenna gain around 9.7 dB at broadside which is improved by 6.2 dB in comparison with the primary aperture antenna without the AMC structure. The thin antenna profile of λ/37.5 is achieved at 10 GHz for 5G evolution. The emission property in an AMC structure herein contributes to the development of a low-profile and high-gain planar antenna for a compact wireless component.
Keywords: Antenna gain; Advanced Antenna and Metasurface Technologies